2021
DOI: 10.3390/ijerph18094520
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Hilly Environment on Depressive Symptoms among Community-Dwelling Older Adults in Japan: A Cross-Sectional Study

Abstract: Although some neighborhood environmental factors have been found to affect depressive symptoms, few studies have focused on the impact of living in a hilly environment, i.e., land slope, on depressive symptoms among rural older adults. This cross-sectional study aimed to investigate whether a land slope is associated with depressive symptoms among older adults living in rural areas. Data were collected from 935 participants, aged 65 years and older, who lived in Shimane prefecture, Japan. Depressive symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This longitudinal four-year follow-up study was conducted using data collected as part of the Shimane CoHRE Study in Shimane Prefecture. It targeted lifestyle-related diseases through the collection of data concerning medical history, lifestyle, and cognitive function during annual municipal health examinations [13][14][15][16].…”
Section: Design Setting and Samplementioning
confidence: 99%
“…This longitudinal four-year follow-up study was conducted using data collected as part of the Shimane CoHRE Study in Shimane Prefecture. It targeted lifestyle-related diseases through the collection of data concerning medical history, lifestyle, and cognitive function during annual municipal health examinations [13][14][15][16].…”
Section: Design Setting and Samplementioning
confidence: 99%
“… 8 A study also showed that rural mountain residents walked up and down steep slopes on a daily basis, which increased the mechanical load on their bodies and may lead to musculoskeletal disorders such as knee and low back pain. 9 Therefore, this study hypothesized that the prevalence of LBP and associated factors in mountainous areas would be different from those in flat areas due to their various topographical characteristics, labor characteristics, and residents’ lifestyles. In addition, the geographical constraints of mountainous areas lead to limited transportation, relative economic backwardness, and scarce medical resources.…”
Section: Introductionmentioning
confidence: 99%